2021
DOI: 10.1002/hsr2.409
|View full text |Cite
|
Sign up to set email alerts
|

Maternity continuum of care and its determinants among mothers who gave birth in Legambo district, South Wollo, northeast Ethiopia

Abstract: Background Maternity continuum of care is the continuity of maternity health care services that a woman uses for antenatal care, skill birth attendant, and postnatal care. Maternal and child mortality is still big challenge in Ethiopia. Little is known about continuum of maternity care in Ethiopia and where the study area in the district revealed that there is a big discrepancy in the completion of maternity care. Objective Assessment of maternity continuum of care and associated factors among mothers who gave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
1
11
3
Order By: Relevance
“…The possible explanation for the variation could be the difference in the MCH coverage indicators incorporated in the summary indices. Our study finds that the overall completion of the COC was two per cent which was lower than that reported in the previous studies [12,27,30,36]. This variation could be explained by the difference in the measurement of the COC as we used the recently modified and more comprehensive coverage index [17].…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…The possible explanation for the variation could be the difference in the MCH coverage indicators incorporated in the summary indices. Our study finds that the overall completion of the COC was two per cent which was lower than that reported in the previous studies [12,27,30,36]. This variation could be explained by the difference in the measurement of the COC as we used the recently modified and more comprehensive coverage index [17].…”
Section: Discussioncontrasting
confidence: 67%
“…At the lower quantiles, women who didn't intend the recent pregnancy had a lower COC compared to their counterparts. Studies showed that the completion of maternity care was higher among mothers whose pregnancy was intended [11,27]. Women with an unintended pregnancy may experience associated psychological issues such as stress and fear stigma from their partners or family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in line with a study conducted in Nigeria (18.5%) (33), India (19%) (34), and the Dabat and Gondar Zuria districts of the Northern Gondar zone (21.6%) (26). However, it is higher than studies conducted in Cambodia (5%) (18), Ghana (7.9%) (35), Tanzania (10%) (25), Ethiopia (6.56% and 9.1%) (19, 28), Arba Minch Zuria district (9.7%) (30), Legambo district of South Wollo zone (11.2%) (36), and West Gojjam zone (12.1%) (29). The possible reason might be attributed to the time difference between the studies, and there could be an improvement in the accessibility of health services, which in turn improves the utilization of maternity care services.…”
Section: Discussionmentioning
confidence: 91%
“…The other reason might be the difference in the study area in which mothers from the current study were mostly rural dwellers, less educated, and had inadequate knowledge of the importance of having maternity care services in a continuum of care pathway. Moreover, the previous studies reported as maternity continuum of care was completed when mothers attended at least one ANC visit, had childbirth attended by SBA, and had at least one postpartum checkup within 6 weeks of delivery, and/or mothers attended ANC-4+ visits, had childbirth attended by SBA, and had one health checkup within 48 h or 6 weeks postpartum period ( 19 21 , 26 – 31 , 36 ). As a result, the estimation of an outcome variable might be increased when compared with this study which considered maternity continuum of care was completed for mothers who attended ANC-4+ visits, had childbirth attended by SBA, and had at least one health checkup either for themselves or for their newborns within the first week of the postpartum period.…”
Section: Discussionmentioning
confidence: 99%